Integration of Artificial Intelligence and Performance of Broadcasting Companies in Nigeria - Akintayo, Atinuke Olubukade; Olugbenga Charles Adewale; Msughter Tsenongo; Mobolaji Grace Akintaro (Britain International for Academic Research (BIAR) Publisher, 2026)
This conceptual paper examines how Artificial Intelligence (AI) integration influences the operational, audience, and economic performance of broadcasting organizations in Nigeria. Drawing on recent scholarly and industry insights, the paper explores AI-driven tools such as automated editing, audience analytics, and content personalization. Findings suggest that while AI enhances productivity and viewer engagement, adoption remains constrained by financial limitations, return on investment uncertainties, infrastructural deficits, skills gaps, and ethical concerns. The study concludes that sustainable integration requires investment in capacity building, localized AI development, and robust digital policies.